Devolepment Strategy Analysis of Leading Business for Fisheries Sector in Situbondo Regency - Ramli, Ramli; Muqsith, Abdul; Rasidi, Moh. (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
The leading business of fisheries sector in the Situbondo District is faced with problems even though it also benefits from government support. Based on these problems and advantages, this research aims to develop leading businesses of fisheries sector in the Situbondo District through the formulation of appropriate business development strategies. The analysis method used to formulate this strategy is SWOT and QSPM analysis. The results of the SWOT analysis recommend that leading businesses of fisheries sector implement survival strategies. The priority strategies based on the QSPM matrix are 1) developing the capacity of fisheries business actors, 2) increasing supply chain performance to increase the competitiveness of fisheries businesses, 3) supporting Government policies in creating a fair fisheries business climate, 4) making production plans based on demand/market, 5) optimizing upstream production activities (catching and cultivation) through environmentally friendly production control and adequate infrastructure support, 6) controlling the quality of fish catches through providing supporting facilities and infrastructure, and 7) increasing production results by optimizing assistance provided by the Government.